2014
DOI: 10.1007/s10461-014-0947-0
|View full text |Cite
|
Sign up to set email alerts
|

“I Have Remained Strong Because of That Food”: Acceptability and Use of Lipid-Based Nutrient Supplements Among Pregnant HIV-Infected Ugandan Women Receiving Combination Antiretroviral Therapy

Abstract: We evaluated the acceptability and use of macronutrient supplementation among HIV-infected pregnant Ugandan women receiving antiretroviral therapy in a clinical study (NCT 00993031). We first conducted formative research among 56 pregnant and lactating women to select a supplement regimen. Acceptability and use of the supplementation regimen [35 sachets of lipid-based nutrient supplements (LNS) and 4 or 6 kg of instant soy porridge for the household provided monthly] were evaluated among 87 pregnant women. Org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Accordingly, our qualitative interviews have revealed that PLHIV perceived the LNS as ‘beneficial in their recovery’ and ‘protective against the adverse effect of ART’ . The perceived beneficial effect of macronutrient supplements by PLHIV has also been reported in a Ugandan study . Another study found that PLHIV perceived ART as harmful when taken without adequate food .…”
Section: Discussionsupporting
confidence: 62%
“…Accordingly, our qualitative interviews have revealed that PLHIV perceived the LNS as ‘beneficial in their recovery’ and ‘protective against the adverse effect of ART’ . The perceived beneficial effect of macronutrient supplements by PLHIV has also been reported in a Ugandan study . Another study found that PLHIV perceived ART as harmful when taken without adequate food .…”
Section: Discussionsupporting
confidence: 62%
“…In a food‐insecure setting such as south‐central Niger, improvements in the nutritional status of pregnant women can be facilitated with increased availability and access to foods that are affordable, beneficial, and acceptable to women at all stages of their pregnancy. Efforts to increase the availability of imported fortified nutritious foods with high consumer acceptability (Young et al, ), coupled with increased access to these items in village marketplaces through targeted interventions such as conditional cash transfers, could improve maternal nutrition among food‐insecure, rural Nigerien women. Efforts to integrate salient terms and discourses identified in this study into programming strategies, for example, culturally appropriate social and behaviour change communications promoting increased consumption of leafy green vegetables and other local nutrient‐rich produce during pregnancy, could help amplify gains in maternal nutrition achieved by the previously recommended market‐level interventions (Lamstein et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous qualitative and mixed-methods studies have been conducted on the acceptability and utilization of IFA [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ], MMN [ 18 , 19 , 20 , 21 ], and LNS [ 16 , 22 , 23 ] in community settings in low-income countries. Measured levels of adherence to supplementation protocol have varied widely in these studies, from 95% in Mali [ 18 ] to 47% in Cambodia [ 12 ].…”
Section: Introductionmentioning
confidence: 99%